Applications of 555 Timer for Development of Low-Cost System - AlShidani S.; Alshabibi S.; Tabrez M.; Kumar K.; Bakhsh F.I. (My University, 2025)
- NE555 is a low cost chip that can be programmed to act as Mono-stable, Bi-stable, or astable multivibrator. This chip is widely used to design electronics circuits that require a single-bit data to function. In this paper, the application of NE555 to develop a low-cost system is discussed. The objective of the work is to design and develop a low cost and Automatic Irrigation Water system and a Clap-Switch using NE555 and mic sensor. These days automatic water irrigation system is used in Gardens, Parks, Stadiums, roadside gardens to minimize the labor cost water losses. Low cost automatic irrigation system shall help automation of gardens/fields irrigation at larger level. NE555 is also found its application to develop a system that can work by clapping sound, especially in design of household appliances switch. This system (clap-switch) might be very useful for differently abled person or children. This paper is a work of under-graduate student project that discuss the design, simulation, and prototype development of low cost automatic irrigation system and a clap-switch using NE555. © 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.